PERANAN SEKTOR NON PERTANIAN TERHADAP PENDAPATAN RUMAH TANGGA PETANI BERLAHAN SEMPIT - A. ROZANY NURMANAF (Program Studi Agribisnis, Fakultas Pertanian, Universitas Udayana Jalan PB.Sudirman Denpasar, Bali, Indonesia. Telp: (0361) 223544 Email: soca@unud.ac.id)
The objective of study is to identify non agricultural sector role on householdincome sources of small sized cultivating farmers. By direct interview, data collectedin covering househld income structure by elevation, agroecosystem and accessibilityof the region. Analysis shows that the role of non agricultural sector is dominant inlow land area with the agroecosystem paddy field which has a good physicalaccessibility. Although the activities in the region vary, the important contribution onhousehold income are limited just on several activities, like trading, non agriculturallabour and money sending from the household member who work outside of theregion. That’s why household income in this area, dominantly supported by theactivities which have skill and capital. On the other hand, in high land area withagroecosystem of dry land and bad accessibility, non agricultural activities arelimited. Household income of small sized cultivating farmers are dominated by thecontribution of agricultural sector activities which include paddy field farming system,dry land farming system, agricultural labour and livestock farming system. As asource of income, non agricultural activities are limited, just came from the activitieswhich have low labour productivity. Consequently, income level of society in theregion are lower.